(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
With the expansion of Information and Communication Technology (ICT), there has been anincrease in internet and social media use. As a result, new types of abuse and violence against womenhave emerged in the internet world.As a result, new types of abuse and violence against women haveappeared in the internet world,such as cyber stalking, circulation of sexual images without consent, cyberbullying, revenge porn and trolling, etc. Such acts have restricted women’s freedom of expression,violating their fundamental rights and human rights. This causes adverse effects not only on the victimwomen but also on our society and families. In order to prevent violence against women, comprehensiveamendments were made through the Criminal Law (Amendment) Act, 2013 in the Indian Penal Code,1860, the Code of Criminal Procedure, 1973, and the Indian Evidence Act, 1872. This made provisionsrelating to violence against women more rigorous. This amendment act 2013 also incorporated newforms of violence against women related to ICT and social media, such as voyeurism, stalking, disrobinga woman, sexual harassment, and enhanced punishment. However, despite such inclusions andstringent amendments inlaws, women face continuous violence online. The irony is that despite all theselegislative measures, most instances of online violence go unreported. Nevertheless, the Indian judicialsystem has set certain landmark judgments to combat online violence against women. Thus, legislativeand judicial development in India with respect to online violence against women has set goodprecedents and the future course of action.